2021
DOI: 10.2147/amep.s310181
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Usage in Improving English Language Proficiency from the Viewpoint of Medical Students

Abstract: Background: In the world today, many people use various communication technologies, like as computer-aided equipment, the internet, and so on. In information communication technologies, people use social media as one of the tools with which to exchange their ideas in everyday communications. Hence, the present study aimed at examining social media usage in improving English language proficiency from the viewpoint of medical students among Ethiopian public university students. Methods: A descriptive survey desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Using English when communicating on social media platform not only provides an opportunity to practice the language, but also it improves the users" knowledge (perception) of how to use "micro" and "macro" language skills and broaden communication and interaction (Desta, et al, 2021). Desta et al (2021) found evidence of the positive impact of social media on the English proficiency of university medical students in Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Using English when communicating on social media platform not only provides an opportunity to practice the language, but also it improves the users" knowledge (perception) of how to use "micro" and "macro" language skills and broaden communication and interaction (Desta, et al, 2021). Desta et al (2021) found evidence of the positive impact of social media on the English proficiency of university medical students in Ethiopia.…”
Section: Literature Reviewmentioning
confidence: 91%
“…They argued that EFL learners' engagement in digital learning activities such as watching English videos, reading news online, and posting English content, increases their motivation to communicate in a foreign language. Using a mixed method design, Zarrinabadi et al (2021) investigated the influence of flipped learning approach on EFL learners' willingness to communicate. They used the Telegram application to assign learners pre-class activities.…”
Section: The Notion Of Willingness To Communicatementioning
confidence: 99%
“…According to Wilde and Hsu (2019), vicarious experiences, as the second source of self-efficacy, are concerned with social comparison of a person's performance to that of others with similar abilities. El-Abd and Chaaban (2021) asserted that observing others' comparable capabilities can improve one's self-efficacy by approving the sufficiency of his/her knowledge, abilities, and approaches. Verbal persuasion, the third source of selfefficacy, refers to "socially persuasive feedback, comments by significant others regarding one's performance" (Bandura, 1997, p. 20).…”
Section: The Notion Of Self-efficacymentioning
confidence: 99%
“…In remote study conditions during the COVID-19 pandemic, the use of digital tools and social media platforms became imperative for medical and dental medical education for information retrieval, sharing of learning materials, and video meetings and discussions [4,5]. These tools were often used for both academic and non-academic purposes among students and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that dental students use more than one social media application with Facebook being the most used platform among students in the United States and the United Kingdom [2][3][4][5][6][7][8]. The second most favored platforms were YouTube and Instagram.…”
Section: Introductionmentioning
confidence: 99%